A Multilayer T-Septum Substrate Integrated Waveguide Filter. Issue 4 (19th May 2017) - Tan, L.; Xu, Z. Q.; Chen, Z.; Huang, S.
ABSTRACT: A multilayer T-septum structure and its application to a substrate integrated waveguide filter are presented. Coupling mechanisms in a T-septum structure, including stacking vertical layer and adjacent common sidewall, are discussed in detail. The T-septum resonance cavity exhibits not only excellent parasitic response characteristics, but also features of a miniature structure. The proposed filter with fourth-order T-septum resonators has two transmission zeros, which can be adjusted flexibly by controlling the coupling strength and manner. With the assistance of the low temperature co-fired ceramic multilayer structure and refined coupling structure, the proposed filter has a more compact size while maintaining high selectivity. A demonstration filter is designed, fabricated, and measured to validate the proposed structure. Measured results are provided showing good performance and agreement with the simulated examples.